2021
DOI: 10.4236/wjet.2021.91011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Project Consultants’ Performance and Project Success in the Rwandan Construction Industry

Abstract: As discovered, today's Rwandan construction industry is developing day by day, which plays a very important role in the country's economic growth. In the construction industry, project consultants play a very significant role in providing services for such projects. The project consultants provide services from the beginning of the project to the completion of the project. Using project consultants is very useful for construction projects because it can ameliorate project efficiency and effectiveness. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…, 2014). This does not seem to be unique to Jordan since authors in other countries have also reported similar problems (Masengesho et al. , 2021).…”
Section: Discussion Of the Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…, 2014). This does not seem to be unique to Jordan since authors in other countries have also reported similar problems (Masengesho et al. , 2021).…”
Section: Discussion Of the Resultsmentioning
confidence: 53%
“…Also, these results could be further explained by research which points to a weak contractor-consultant relationship in Jordan and the little authority vested in the consultants by clients (Abu-Reishah and Hiyassat, 2021;Sweis et al, 2014). This does not seem to be unique to Jordan since authors in other countries have also reported similar problems (Masengesho et al, 2021).…”
Section: Jordanian Construction Industrymentioning
confidence: 95%
See 3 more Smart Citations